Flexible and Transparent Composite Electrode with 3D Freestanding Architecture for Dopamine Monitoring. (13th October 2022) - Zhang, Xuan‐Yi; Xu, Jian‐Long; Ren, Shan; Yang, Qian; Liu, Mei‐Jia; Chang, Xing‐Hua; Sun, Yi‐Lin; Gao, Xu; Zhong, Ya‐Nan; Liu, Yan‐Hua; Wang, Sui‐Dong
Abstract: Development of a flexible, transparent, and air‐permeable dopamine (DA) sensor is highly desirable for fully integrated optoelectrochemical probes, which can provide a useful tool for closed‐loop control and monitoring neural activities. Herein, a 3D freestanding architecture, which integrates a flexible and transparent metallic micromesh as the "core" with DA sensitive poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) as the "shell, " has been developed for DA monitoring. The freestanding micromesh electrode shows not only high mechanical flexibility (without apparent performance variation after 100 bending times), high optical transparency (≈85% at 550 nm), and air permeability (≈2600 mm s −1 at 10 Pa), but also excellent DA sensing performance such as a sensitivity up to 1650 µAcm −2 mM −1, wide linear range from 1 × 10 −6 to 1000 × 10 −6 m, a low limit of detection (LOD) of 0.27 × 10 −6 m, high selectivity and high stability. The outstanding performance may arise from the core‐shell micromesh configuration, which combines high electrical conductivity of the Ni micromesh and high electrocatalytic activity of the PEDOT:PSS layer for DA oxidation. Such 3D freestanding architecture offers a simple and effective methodology to construct implantable biosensors for monitoring of DA and other neurotransmitters in the brain. Abstract : Our work demonstrates a flexible and transparent composite electrode with 3D freestanding architecture for dopamine (DA) monitoring. The insights into the construction of flexible transparent DA sensing electrode via the "metallic mesh 'core' ‐ sensitive element 'shell'" configuration will be of interest to the fields related to electrochemical sensing.